The Importance Of Understanding And Application Of Marketing Strategies For Household Micro, Small & Medium Enterprise (Msme) Products On Social Media Networks - Teguh Setiawan Wibowo; Dwi Bhakti Iriantini (CV. AFDIFAL MAJU BERKAH, 2022)
With the development of increasingly sophisticated technology and communication, social media tends to be used as the main pillar in delivering information digitally, communicating in business, helping product marketing, communicating with customers and suppliers, and reducing costs that must be incurred conventionally. Social media that are usually used are those that are open and whose existence is recognized by the wider community and are made in various forms of platforms with a structured system or known as social media networks. One of the users of the social media network is household MSME actors, especially those affected by Covid-19 which has caused a decrease in the number of buyers in MSME businesses. With easy and fast access to social media networks, MSME actors are expected to be bolder in promoting their products because there is no time limit on their use and the wide range of product marketing areas to the global market, thus making social media networks an effective marketing medium. However, household MSME products still have obstacles in penetrating the export market, namely obstacles in quality standards. To overcome this, household MSME actors need to understand and apply marketing strategies that support efforts to increase competitiveness by using social media networks in the face of increasingly fierce business competition. MSME actors must also make extensive use of social media networks in developing their businesses so that they can progress quickly and be ready globally. In this article, the discussion focuses on the importance of understanding and applying marketing strategies for household MSME products on social media networks.